2018
DOI: 10.1177/0960327118756720
|View full text |Cite
|
Sign up to set email alerts
|

Urinary bisphenol A levels in Turkish girls with premature thelarche

Abstract: There is a growing concern over the timing of pubertal breast development and its possible association with exposure to endocrine disrupting chemicals (EDCs), such as bisphenol A (BPA). BPA is abundantly used to harden plastics. The aim of this study was to investigate the relation between premature thelarche (PT) and BPA by comparing the urinary BPA levels of PT girls with those of healthy subjects. Twenty-five newly diagnosed nonobese PT subjects (aged 4-8 years) who were admitted to the Pediatric Endocrinol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 73 publications
0
12
1
Order By: Relevance
“…Studies demonstrate how this EDC is associated with premature thelarche, precocious puberty and pubertal development [15][16][17].…”
Section: Bpamentioning
confidence: 99%
“…Studies demonstrate how this EDC is associated with premature thelarche, precocious puberty and pubertal development [15][16][17].…”
Section: Bpamentioning
confidence: 99%
“…BPA has weak ER agonist activity at lower concentrations but can also compete with endogenous estrogens for binding, and they have antiandrogenic properties at higher concentrations [28]. Epidemiological studies on BPA and puberty have produced inconsistent results (Table 2) [29-51]. Serum or urinary BPA concentrations were significantly associated with premature thelarche [39,51], precocious puberty [32,37,44,50], and earlier pubertal development [48].…”
Section: Bisphenol Amentioning
confidence: 99%
“…Epidemiological studies on BPA and puberty have produced inconsistent results (Table 2) [29-51]. Serum or urinary BPA concentrations were significantly associated with premature thelarche [39,51], precocious puberty [32,37,44,50], and earlier pubertal development [48]. However, other studies have reported no significant relationship [29-31,33-36,38,40-43,47] or later onset of puberty or menarche [45,46,49].…”
Section: Bisphenol Amentioning
confidence: 99%
“…In the same vein, contradictory findings have also been reported in girls, where some studies have suggested an association between increased urinary levels of BPA and altered puberty (Durmaz et al. 2014, 2018; Kasper-Sonnenberg et al. 2017; McGuinn et al.…”
Section: Introductionmentioning
confidence: 99%